Extracellular vesicles enclosed‐miR‐421 suppresses air pollution (PM2.5)‐induced cardiac dysfunction via ACE2 signalling. Issue 5 (10th May 2022) - Wang, Hongyun; Wang, Tianhui; Rui, Wei; Xie, Jinxin; Xie, Yuling; Zhang, Xiao; Guan, Longfei; Li, Guoping; Lei, Zhiyong; Schiffelers, Raymond M; Sluijter, Joost P G; Xiao, Junjie
Abstract: Air pollution, via ambient PM2.5, is a big threat to public health since it associates with increased hospitalisation, incidence rate and  mortality of cardiopulmonary injury. However, the potential mediators of pulmonary injury in PM2.5 ‐induced cardiovascular disorder are not fully understood. To investigate a potential cross talk between lung and heart upon PM2.5 exposure, intratracheal instillation in vivo, organ culture ex vivo and human bronchial epithelial cells (Beas‐2B) culture in vitro experiments were performed respectively. The exposed supernatants of Beas‐2B were collected to treat primary neonatal rat cardiomyocytes (NRCMs). Upon intratracheal instillation, subacute PM2.5 exposure caused cardiac dysfunction, which was time‐dependent secondary to lung injury in mice, thereby demonstrating a cross‐talk between lungs and heart potentially mediated via small extracellular vesicles (sEV). We isolated sEV from PM2.5 ‐exposed mice serum and Beas‐2B supernatants to analyse the change of sEV subpopulations in response to PM2.5 . Single particle interferometric reflectance imaging sensing analysis (SP‐IRIS) demonstrated that PM2.5 increased CD63/CD81/CD9 positive particles. Our results indicated that respiratory system‐derived sEV containing miR‐421 contributed to cardiac dysfunction post‐PM2.5 exposure. Inhibition of miR‐421 by AAV9‐miR421‐sponge could significantly reverse PM2.5 ‐induced cardiac dysfunction in mice. We identified that cardiac angiotensin converting enzyme 2 (ACE2) was a downstream target of sEV‐miR421, and induced myocardial cell apoptosis and cardiac dysfunction. In addition, we observed that GW4869 (an inhibitor of sEV release) or diminazene aceturate (DIZE, an activator of ACE2) treatment could attenuate PM2.5 ‐induced cardiac dysfunction in vivo. Taken together, our results suggest that PM2.5 exposure promotes sEV‐linked miR421 release after lung injury and hereby contributes to PM2.5 ‐induced cardiac dysfunction via suppressing ACE2.